Crowdsourcing in Software Testing: Opportunities for Software Companies - Aujla, Paramjit Singh (Digital Repository of Theses - SSBM Geneva, 2024)
This research is being conducted to explore and understand how effectively crowdsourcing techniques are utilised in the Information Technology industry today to build software products. The core question posed is: What are the business strategies and practices of IT Product development companies to build high-quality software products at a low cost?? The goal is to analyse data from various industry papers, organisations and products in the Information Technology industry and formally define the crowdsourcing techniques and practices beneficial for software product development. The research utilized a qualitative approach, using an online interview questionnaire and semi-structured interviews. The interview questionnaire was shared with a wider audience working in the IT Industry with specialization skills in software testing, or development over social media platforms like LinkedIn.com. The Semi-structured interviews were conducted through using channels such as Zoom, and face-to-face interactions. The study focused on the software project experiences of various individuals having experience in the IT Industry, ranging from Testers to mid-senior and executive positions. All interviewees were carefully selected from the global locations to learn the variety of experiences and build an understanding of the usage of Crowdsourcing in Software Testing. Data were collected through interview questionnaires, interviews and web data scrapping. Abductive reasoning methods were employed in exploring Crowdsourcing awareness, such as the adoption and use of Crowdsourcing, the impact of Crowdsourcing on individuals and organizations, and the emergence of testing strategies based on Crowdsourcing. The study revealed that Crowdsourcing for software testing is still a new field for many people. Software companies still prefer direct vendor contracts or full-time people to get the job done. It is observed that key concerns are falling in the areas of security, team management and infrastructure. Based on their experiences, crowdsourcing will evolve as a field: With the increasing demand for software products and services, the adoption of crowdsourced testing is expected to grow significantly. More companies are likely to embrace crowdsourced testing as a viable alternative to traditional testing methods, especially for large-scale or complex projects., Advanced testing tools: Crowdsourced testing platforms are likely to incorporate advanced testing tools and technologies such as AI, machine learning, and automation to improve testing accuracy and efficiency., Improved quality control: Crowdsourced testing platforms are likely to implement better quality control mechanisms to ensure that testing is conducted accurately and thoroughly. This could include improved tester selection processes, better testing guidelines, and more comprehensive reporting and feedback mechanisms.